Aligning assessment with the needs of work-integrated learning: the challenges of authentic assessment in a complex context. Issue 2 (17th February 2020) - Ajjawi, Rola; Tai, Joanna; Huu Nghia, Tran Le; Boud, David; Johnson, Liz; Patrick, Carol-Joy
Abstract: Work-integrated learning (WIL) is a feature of university courses, both in professional areas, where it is commonplace, but also across many different disciplines. Assessment of WIL can be complex as it involves parties and settings external to the university, and it can be problematic because of difficulties in aligning learning activities during placements with what is or can be assessed by the university. This paper explores the relationship between students' placement experiences and accompanying assessments in contexts where activities are tightly coupled with the curriculum, and in those where it is not. It draws on a qualitative analysis of student interviews and drawings by the interviewees of their WIL experiences, supplemented with analysis of unit guides. Our findings highlight that students' perceptions of authenticity of assessment were undermined by misalignments between the student, university and industry. Assessment authenticity was perceived by students as based on alignment between their current and future selves in the assessment process, involvement of industry supervisors and relevance of placement activities to assessment activities. The paper discusses the complexity of coordination of educational activities with external partners, especially when one party drives assessment. It then suggests a reframing of WIL assessment to promote alignment and authenticity.